Comercialização do açaí como instrumento de etnodesenvolvimento na comunidade extrativista Boa Esperança, cidade de Curralinho - PA - MORAES, Letícia Santiago de (2022)
This Plan of Action is a collective project in the context of an alliance between peoples and academics, and its elaboration is based on the demands of the extractive community Boa Esperança, in the town of Curralinho in the state of Pará. The objective is to create better conditions for the commercialization of Açaí by the Cooperativa dos Productores Agroextrativistas do Rio Pagão (COPA), eliminating middlemen and making it possible to sell the products directly to the consumer at a fair price. The elaboration of this plan took place by way of participatory research conducted during a period of action resarch and contributions from the discussions with the teachers and classmates during the teaching period, with those periods being preconceived in the Political Educational Project of the Bachelor’s degree course in Ethno-Development of the Federal University of Pará (UFPA). Addtional sources were bibliographical surveys and mobilizations in the community regarding its problems and potentials. Some of the collectively constructed strategies highlight the protagonism of the community, the historical processes of struggle and resistance, and the importance of the autonomy of the community in the management of its territories and resources. According to the research carried out together with the community Boa Esperança, my community of origin, the communitarian extractivism of açaí production and its commercialization resisted during the hard years of exploitation of the local wood resources. In the 1990s, the family income in this community was based on the predatory removal of wood and palmtree fruits, latex exploitation and seed collection. Nowadays açaí is our main basis of nutrition and income, but the marketing channels are restricted to the brokers and the sale to the market fair of the town of Curralinho. The lack of alternatives for commercialization results in low sales prices during the months of high production (July to December). In view of the objective and the problem raised, this Plan of Action proposes to enable access to the government-controlled Institutional Markets for purchase of rural foodstuffs (Programa de Aquisicao de Alimentos (PAA), Programa Nacional de Alimentacao Escolar (PNAE)), the maintenance and improvement of the açaí trading locale and the implementation of a thirteenth salary for extractivists.